TRANSLATION OF CULTURAL TERMS - Nishonova Shaxnoza Muhammedjanova (Galaxy International Interdisciplinary Research Journal, 2023)
In this research Cultural translation is studied through cultural anthropology, a field of anthropology focused on cultural issues among humans. This discipline questions translation through cultural differences. Indeed, translation studies are not only based on language issues, but also on cultural contexts between people.